2010
DOI: 10.4103/0019-509x.73574
|View full text |Cite
|
Sign up to set email alerts
|

The effect of age on the bacteria isolated and the antibiotic-sensitivity pattern in infections among cancer patients

Abstract: This suggests that empirical antibiotic therapy needs to be changed on the basis of the age of the patient. It also appears that combination therapy is essential for the empirical treatment of infections in elderly patients with cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…The main characteristics and results of the 24 studies published since 2007 that described the species distribution of bacterial isolates in patients with malignancies and febrile neutropenia are summarized in Table 1 [6-13,14 & , [15][16][17][18][19][20][21][22][23][24]25 & , [26][27][28][29]. In general, there is a certain level of heterogeneity among these studies.…”
Section: Current Trends In the Epidemiology Of Bacterial Infections Imentioning
confidence: 99%
See 4 more Smart Citations
“…The main characteristics and results of the 24 studies published since 2007 that described the species distribution of bacterial isolates in patients with malignancies and febrile neutropenia are summarized in Table 1 [6-13,14 & , [15][16][17][18][19][20][21][22][23][24]25 & , [26][27][28][29]. In general, there is a certain level of heterogeneity among these studies.…”
Section: Current Trends In the Epidemiology Of Bacterial Infections Imentioning
confidence: 99%
“…Secondly, in 13 of the studies the bacterial isolates were collected during episodes of febrile neutropenia [7,8,10,11,13,14 & ,17,18,20,21,26,29]. Thirdly, the bacteria were isolated from different sources; 16 studies included BSIs only [7,8,[10][11][12]14 & , 15-18, 21,22,24,25 & ,27,29], and eight studies isolated the bacteria from clinical (and/or surveillance) samples for which the percentage of bloodstream isolates ranged from 42.9 to 74.8% in five studies [6,19,23,26,28] and was not reported in the remaining three [9,13,20]. Thirdly, the bacteria were isolated from different sources; 16 studies included BSIs only [7,8,[10][11][12]14 & , 15-18, 21,22,24,25 & ,27,29], and eight studies isolated the bacteria from clinical (and/or surveillance) samples for which the percentage of bloodstream isolates ranged from 42.9 to 74.8% in five studies [6,19,23,26,28] and was not reported in the remaining three [9,13,20].…”
Section: Current Trends In the Epidemiology Of Bacterial Infections Imentioning
confidence: 99%
See 3 more Smart Citations